(untitled) (CIPEEX, 2023)
Cardiovascular diseases are the leading causes of death worldwide, and the university work environment, with its distinct demands, can contribute to factors that impair cardiovascular health. The objective of the study was to assess the cardiovascular health of university workers. This is a descriptive study conducted with 121 university employees. To assess cardiovascular health, it was done through the recommendation of the American Heart Association, which established seven metrics (diet, physical activity level (PAL), smoking, body mass index (BMI), fasting blood glucose, total cholesterol, systemic blood pressure (SBP)), descriptive data. The results identified that, when analyzing the average values, the BMI, PA, diet, and SBP metrics were at intermediate levels. The metrics that had the highest percentage of poor CVS were NAF (30.6%), BMI (17.4%), and BP (23.1%). It is concluded that 25% of the employees had poor SCV. And the university work environment needs public policies for the promotion of cardiovascular health.